Commentary - Martienssen, Rex D (Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1931)
'...Why not try nothing?"
Keywords: Martienssen, Rex D; News Building, New York; Raymond Hood